CD19-directed chimeric antigen receptor T-cell therapy: what can we learn from the haematologist? - Marie José Kersten; Maria Theresa Kuipers (Lupus Science and Medicine)
CD19-directed chimeric antigen receptor (CAR) T-cell therapy, originally developed for haematological malignancies, has recently emerged as a promising therapy for patients with autoimmune diseases. By selectively depleting CD19-positive B-cells, this therapy brings a new approach in resetting immune dysregulation and potentially providing long-term remission for patients with a refractory disease. Recent reports have highlighted its effectiveness in conditions such as SLE, systemic sclerosis and myositis. However, while these early results are encouraging, questions remain regarding strategies for optimal patient selection and minimising toxicity on the short and long term. The experiences with CD19 CAR T-cell therapy in haematology may offer valuable insights for immunologists and rheumatologists. This article reviews the key principles learnt in haematology, the results and the mechanisms behind its efficacy, toxicities, and the challenges that need to be addressed for its broader application in clinical practice.